2001
DOI: 10.1002/j.1551-8833.2001.tb09230.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatability of Mtbe‐contaminated groundwater by Ozone and Peroxone

Abstract: A combination of ozone and hydrogen peroxide (known as peroxone) was studied as a treatment alternative for removing methyl tertiary butyl ether (MTBE), a common fuel oxygenate. The authors investigated the effects of oxidation of ozone and peroxone on MTBE in Santa Monica, Calif., groundwater. Experiments conducted in a large‐scale, semibatch reactor demonstrated that peroxone (at a peroxone ratio of 1.0, with applied ozone doses of ≤10 mg/L) was more consistently effective in oxidizing MTBE than was ozone al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The initial concentration of SMX in ozonated samples was 0.150 mM. This hydrogen peroxide flow was chosen to keep the overall H 2 O 2 /O 3 molar ratio below 0.5, which corresponds to the overall stoichiometry of the O 3 /H 2 O 2 reaction, thereby avoiding an excess of hydrogen peroxide and the subsequent hydroxyl radical scavengers [17][18][19]. pCBA was used as probe compound to assess the presence of hydroxyl radicals in the reaction mixture.…”
Section: Ozonation Experimentsmentioning
confidence: 99%
“…The initial concentration of SMX in ozonated samples was 0.150 mM. This hydrogen peroxide flow was chosen to keep the overall H 2 O 2 /O 3 molar ratio below 0.5, which corresponds to the overall stoichiometry of the O 3 /H 2 O 2 reaction, thereby avoiding an excess of hydrogen peroxide and the subsequent hydroxyl radical scavengers [17][18][19]. pCBA was used as probe compound to assess the presence of hydroxyl radicals in the reaction mixture.…”
Section: Ozonation Experimentsmentioning
confidence: 99%
“…Bromate is a chemical that is formed during the ozonation of natural waters where bromide is present. In environments with a high bromide content such as seawater, bromide concentrations are approximately 65 mg/l (Acero et al, 2001;Chang and Yen, 2000;Liang et al, 2001;West Hertfordshire Health Authority, 2001). The USEPA has set the MCL for bromate at 0.010 mg/l because toxicology studies have shown bromate to be carcinogenic in laboratory animals (USEPA, 1998).…”
Section: Ozonementioning
confidence: 99%
“…During laboratory studies, Liang et al (2001) found that 0 3 alone caused an increase in bromate concentration, but with peroxide to 0 3 ratios of greater than 1.0, a decrease in bromate concentration was realized. Liang et al (2001) determined that the H 2 0 2 in the peroxone treatment reduced aqueous bromine to bromide, resulting in low yields of bromate.…”
Section: Ozonementioning
confidence: 99%
See 2 more Smart Citations